Parents' Experiences and Responses to an Intervention for Psychological Preparation of Children and Families During the Child's Radiotherapy. (March 2018) - Ångström-Brännström, Charlotte; Lindh, Viveca; Mullaney, Tara; Nilsson, Kristina; Wickart-Johansson, Gun; Svärd, Anna-Maja; Nyholm, Tufve; Lindh, Jack; Engvall, Gunn
The aim of this study was to evaluate parents' experiences and responses to a systematic intervention for psychological preparation of children and families during the child's radiotherapy (RT) treatment. In this case-control study at 3 pediatric RT centers, an intervention with a preparatory kit, including age-adjusted information on tablets, gift of a stuffed toy or a pair of headphones, a parent booklet, and toy models of the computed tomography and RT machines was implemented. For evaluation, a mixed methods data collection was conducted. A total of 113 parents of children undergoing RT were included—n = 59 in the baseline group and n = 54 in the intervention group. Health-related quality of life was rated low, but parents in the intervention group expressed less anxiety after the RT compared with the baseline group. They found information suitable for their young children, siblings, and friends were involved and the toy models were used for play. Parents expressed positive feelings due to close interaction with staff and each other within the family. The solutions developed within a human-centered design approach and shaped as a systematic family-centered strategy contributed to parents understanding and coping with the child's RT.